2008
DOI: 10.1103/physrevlett.101.107601
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Polarization Patterns in Flat Epitaxial Ferroelectric Nanoparticles

Abstract: We investigate the effects of a lattice misfit strain on a ground state and polarization patterns in flat perovskite nanoparticles (nanoislands of BaTiO3 and PZT) with the use of an ab initio derived effective Hamiltonian. We show that the strain strongly controls the balance between the depolarizing field and the polarization anizotropy in determining the equilibrium polarization patterns. Compressive strain favors 180 degrees stripe or tweed domains while a tensile strain leads to in-plane vortex formation, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 37 publications
9
78
0
Order By: Relevance
“…14,15 Large quantities of theoretical approaches, i.e., thermodynamic modeling, atomistic level simulations, and first-principle calculations, etc., are focused on studying properties of ferroelectric nanostructures, and want to reveal the finite size effect on ferroelectricity, domain structure and related properties. [16][17][18][19][20][21][22] Recent theoretical simulations and experimental results have shown that ferroelectric nanostructures can exhibit toroidal order of ferroelectric domains. [23][24][25][26][27][28] This so-called vortex domain structure (VDS) is likely to be induced by strong geometric confinements or coupling between order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Large quantities of theoretical approaches, i.e., thermodynamic modeling, atomistic level simulations, and first-principle calculations, etc., are focused on studying properties of ferroelectric nanostructures, and want to reveal the finite size effect on ferroelectricity, domain structure and related properties. [16][17][18][19][20][21][22] Recent theoretical simulations and experimental results have shown that ferroelectric nanostructures can exhibit toroidal order of ferroelectric domains. [23][24][25][26][27][28] This so-called vortex domain structure (VDS) is likely to be induced by strong geometric confinements or coupling between order parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] In spite of these advances, there are still very few experimental investigations on the nanoscale polarization patterns compared with numerous theoretical studies. [11][12][13] Although a few polarization patterns, like vortex-like polarization, have been reported in thin films, 14,15 nanocapacitors, 16 stand-alone nanodots, 17 and nanodot arrays, 18 other possible patterns, like bubble domains or more complex polarization structures analog to those observed in nanomagnets, have rarely been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…A core polarization state may be an indication of a vortex domain, 12 and evidence for such domain states have been presented, 18 wherein it was necessary to use both vertical piezoforce microscopy (VPFM) and lateral piezoforce microscopy (LPFM) to develop a full picture of the polarization state of the nanodot. It may be possible for certain conditions (size, strain, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Polar vortex domains are typically caused by either reduced size in three dimensions, such as in ferroelectric nanodots or nanoislands, without charge compensation on the surfaces [7][8][9], or induced by local external electric fields, e.g., from a piezoresponse force microscope [10,11]. Although spontaneous vortex domains in ferroelectric thin films have been experimentally observed in PbZr x Ti 1-x O 3 and BiFeO 3 (BFO) [12][13][14], the necessary conditions for forming vortex domains in a heterostructure, e.g., a ferroelectric film on a substrate or one-dimensional superlattice (finite size in one dimension) are not known. Furthermore, the usefulness of these observed domains has been questionable due to the inability to reverse the chirality of the static vertices under experimental conditions.…”
mentioning
confidence: 99%
“…Although magnetic vortex domains are well known [1], polar vortex domains have only recently been observed and investigated [2][3][4][5][6]. Polar vortex domains are typically caused by either reduced size in three dimensions, such as in ferroelectric nanodots or nanoislands, without charge compensation on the surfaces [7][8][9], or induced by local external electric fields, e.g., from a piezoresponse force microscope [10,11].…”
mentioning
confidence: 99%